Feasibility of a Breath Test for Monitoring Adherence to Vaginal Administration of Antiretroviral Microbicide Gels. (24th January 2013) - Morey, Timothy E.; Wasdo, Scott; Wishin, Judith; Quinn, Brian; van der Straten, Ariane; Booth, Matthew; Gonzalez, Daniel; Derendorf, Hartmut; Melker, Richard J.; Dennis, Donn M.
Abstract Adherence to microbicide gel use is critical to optimizing effectiveness in preventing human immunodeficiency virus transmission. The authors hypothesized that ester taggants added to vaginal gels would generate exhaled alcohol and ketone metabolites and provide a "breath test" for vaginal gel use. This 2‐arm (vaginal and dermal), randomized, participant‐blinded, pilot study tested this hypothesis. On 8 visits, healthy women (n = 8) received intravaginal taggant (2‐butyl acetate, 2‐pentyl acetate, isopropyl butyrate, or 2‐pentyl butyrate; 30 mg) formulated in hydroxyethylcellulose or tenofovir placebo gel. A second group (n = 4) of women received the same formulations administered dermally on the forearm to determine if skin administration might confound the system. Breath samples were collected using bags before and after taggant administration for 1 hour. Samples were measured using a miniature gas chromatograph and/or gas chromatography–mass spectroscopy for ester taggant, alcohol, and ketone concentrations. After vaginal administration, 2‐butyl acetate, 2‐pentyl acetate, and metabolites were observed in breath, whereas isopropyl butyrate, 2‐pentyl butyrate, and metabolites were not. Some women reported self‐resolving, mild burning (24/64 visits) with vaginal administration or a "bubblegum" taste (7/64 visits). No taggants or metabolites were detected following dermal application. A "breath test" for adherence to antiretroviral vaginal gel application appears physiologically and technically feasible.